Profibrinolytic activity of the direct thrombin inhibitor melagatran and unfractionated heparin in platelet-poor and platelet-rich clots - Semeraro, Fabrizio; Piro, Donatella; Rossiello, Maria R.; Ammollo, Tiziana; Colucci, Mario (Thrombosis and Haemostasis, 2007)
Anticoagulants have been shown to stimulate fibrinolysis principally via inhibition of thrombin-mediated activation of TAFI (thrombin activatable fibrinolysis inhibitor). Their profibrinolytic effect,however,may vary according to their mechanism of action and to the clot composition. We compared the fibrinolytic activity of the direct thrombin inhibitor melagatran with that of unfractionated heparin in platelet-poor (PPP) and platelet-rich (PRP) models consisting of tissue-factor-induced clots exposed to exogenous t-PA (25 ng/ml). In the PPP clot model, both heparin (0.1–0.6 U/ml) and melagatran (20–320 ng/ml) caused a concentration- dependent shortening of lysis time. However, when drug profibrinolytic activity (lysis ratio) was expressed in function of the aPTT prolongation (aPTT ratio), melagatran was more efficient than heparin. In the PRP clot model, melagatran displayed a fibrinolytic activity fairly comparable to that observed in PPP whilst heparin caused a modest reduction of lysis time only at the highest concentrations. Assay of thrombin and TAFIa generation in defibrinated plasma showed that the presence of platelets markedly reduced the ability of heparin,but not that of melagatran, to inhibit the formation of these enzymes. Altogether these data indicate that melagatran is more efficient than heparin in promoting fibrinolysis, particularly in plateletrich clots, and may thus grant a greater antithrombotic activity by enhancing thrombus dissolution.
Keywords: Fibrinolysis; anticoagulants; thrombin; TAFI; platelets